2019
DOI: 10.1111/jcmm.14547
|View full text |Cite
|
Sign up to set email alerts
|

A novel role of kynureninase in the growth control of breast cancer cells and its relationships with breast cancer

Abstract: Breast cancer is the most common malignancy among women worldwide. Kynureninase (KYNU) located in 2q22.2, which was associated with tryptophan utilization and metabolic diseases including cardiac, renal and limb defects syndrome 2. However, the role of KYNU in breast cancer (BC) development remains unclear. The expression of KYNU was examined by immunohistochemistry (IHC) in 137 primary BC tissues, and the correlation of KYNU expression with clinical pathological characteristics and the biomarkers (ER, PR, HER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
1
21
1
Order By: Relevance
“…11 KYNU is involved in various inflammatory and cardiovascular diseases, in addition to several types of cancers, acting via different pathways ( Figure 1). [12][13][14][15] Here we discuss the findings, from the literature, supporting the hypothesis that KYNU is a transcriptional target of CD44 as well as known signalling pathways linking the activation of CD44 by HA to the transactivation of KYNU in promoting breast tumour cell invasion.…”
supporting
confidence: 66%
“…11 KYNU is involved in various inflammatory and cardiovascular diseases, in addition to several types of cancers, acting via different pathways ( Figure 1). [12][13][14][15] Here we discuss the findings, from the literature, supporting the hypothesis that KYNU is a transcriptional target of CD44 as well as known signalling pathways linking the activation of CD44 by HA to the transactivation of KYNU in promoting breast tumour cell invasion.…”
supporting
confidence: 66%
“…15 A study by Lauvrak et al revealed that expression of KYNU was notably downregulated in highly aggressive osteosarcoma cells 14 and recently, Liu et al reported that KYNU played a suppressive role in tumour growth and development in breast cancer. 16 Other studies have shown that KYNU was upregulated in psoriasis and its expression was positively correlated with psoriasis severity and inflammation. 12 As KYNU is related to skin disease and cancers, we investigated whether KYNU has an effect on cSCC.…”
Section: Discussionmentioning
confidence: 97%
“…KYNU is a pyridoxal-5´-phosphate dependent enzyme that catalyzes the cleavage of kynurenine into anthranilic acid (AA) and the cleavage of 3-hydroxykynurenine (3-HK) into 3-hydroxyanthranilic acids (3-HAA) ( Badawy, 2017 ). Drugs have been developed to regulate the expression of KYNU to suppress tumor growth through the Kynurenine pathways, such as in breast cancer ( Liu et al, 2019 ; Liu et al, 2020 ) and melanoma ( Rad et al, 2019 ). It has been demonstrated that TTF2 is able to terminate RNA polymerase II transcription, which has an important function in promoting chromosome segregation and altering protein-DNA interactions ( Jiang and Price, 2004 ; Jiang et al, 2004 ; Cheng et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%